2015
DOI: 10.1002/advs.201500199
|View full text |Cite
|
Sign up to set email alerts
|

Porous Nickel–Iron Oxide as a Highly Efficient Electrocatalyst for Oxygen Evolution Reaction

Abstract: A porous Ni–Fe oxide with improved crystallinity has been prepared as a highly efficient electrocatalytic water oxidation catalyst. It has a small overpotential, a low Tafel slope, and an outstanding stability. The remarkably improved electrocatalytic performance is due to the porous structure, high extent homogeneous iron incorporation, ameliorative crystallinity, and the low mass transfer resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
176
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 272 publications
(184 citation statements)
references
References 58 publications
8
176
0
Order By: Relevance
“…We supposed that the porous structure in Fe/Ni-BTC film generated from BTC is favorable for the OER catalysis, and this result excludes the influence of the small amount of amorphous metal hydroxides or metal oxides that may exist in the Fe/Ni-BTC film. Compared with two similar catalysts that we reported previously, i.e., bulk Ni− Fe oxides and porous Ni−Fe oxides, 10 the Fe/Ni-BTC@NF clearly outperforms the porous Ni−Fe oxide catalyst owing to not only the intrinsic porosity of MOF film but also the periodic arrangement and the homogeneous distribution of metal centers in the MOF film. Moreover, the NF affords a highly conductive macroporous scaffold with high surface area.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We supposed that the porous structure in Fe/Ni-BTC film generated from BTC is favorable for the OER catalysis, and this result excludes the influence of the small amount of amorphous metal hydroxides or metal oxides that may exist in the Fe/Ni-BTC film. Compared with two similar catalysts that we reported previously, i.e., bulk Ni− Fe oxides and porous Ni−Fe oxides, 10 the Fe/Ni-BTC@NF clearly outperforms the porous Ni−Fe oxide catalyst owing to not only the intrinsic porosity of MOF film but also the periodic arrangement and the homogeneous distribution of metal centers in the MOF film. Moreover, the NF affords a highly conductive macroporous scaffold with high surface area.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
“…More importantly, the building block design, rich choice of mixed metal ions, and electrochemical deposition fabrication strategy may pave the way for developing novel heterogeneous OER catalysts with molecular design and tuning abilities showing exceptional electrocatalytic performance for potential large-scale applications.■ ASSOCIATED CONTENT * S Supporting InformationThe Supporting Information is available free of charge on the ACS Publications website at DOI:10.1021/acsami.6b05375. ECD process, N 2 adsorption/desorption isotherms, LSV curves of MOFs samples with different Fe/Ni ratios, cyclic voltammograms, analysis of ECSA, table for OER activities of some benchmark electrocatalysts (PDF) Video S1, controlled potential electrolysis (AVI) *E-mail: bowang@bit.edu.cn.…”
mentioning
confidence: 99%
“…More likely and more preferably, the metal-hydroxyl adduct can give out an electron to the electrode and release a proton to the buffer electrolyte or the proximate ligands to form a metal-oxo species with a high-valence metal center. [146][147][148][149][150][151][152][153][154][155][156] Typically, materials with mixed metal elements display much enhanced activity compared with their single metal counterparts. The nucleophilic attack on the metal-oxo site by a water molecule is a favored reaction to form the OO bond and to subsequently release the O 2 .…”
Section: Electrocatalytic Oxygen Evolutionmentioning
confidence: 99%
“…Thereafter, there are two typical pathways to generate an O 2 molecule based on the metal-oxo species. [7,148,157] Adv. Less likely, two adjacent metal-oxo species may interact together to form the OO bond provided with the proper distance between the two oxygen atoms.…”
Section: Electrocatalytic Oxygen Evolutionmentioning
confidence: 99%
“…Qi et al also reported the improved OER performance of Fe-doped NiO. [189] The Fe-doped NiO annealed up to 200 °C presented the highest catalytic efficiency with η = 487 mV at 62 mA cm −2 for Ni 85 Fe 15 .…”
Section: Rock-salt-type Metal Oxidesmentioning
confidence: 99%